Comparative Study of World Health Organization Recommended Smallpox Vaccine to Prevent Monkeypox - Reas Najla Anugrah; Ahsanal Kasasiah (JURNAL KESMAS DAN GIZI (JKG), 2026)
Background: Monkeypox is a zoonotic disease caused by the monkeypox virus (MPXV) from the Orthopoxvirus genus and has shown a global increase in cases since 2022. Currently, no specific vaccine is available; however, smallpox vaccines provide cross-protection and are recommended by the World Health Organization (WHO) for prevention. Objective: This review aims to compare the efficacy and safety of WHO-recommended smallpox vaccines (MVA-BN, LC16m8, and ACAM2000) in preventing monkeypox. Methods: This literature review searched Google Scholar and Publish or Perish with the keywords “monkeypox vaccine”, “MVA-BN,” “LC16,” “ACAM2000,” “efficacy,” and “safety.” Articles published between 2015 and 2025 were included. Of 155 identified records, 9 met the inclusion criteria and were analyzed. Results: All vaccines were effective in preventing monkeypox through humoral and cellular immune responses. MVA-BN showed the highest efficacy and best safety profile, while LC16m8 provided long-term protection with mild adverse effects. ACAM2000 was effective but associated with mild cardiovascular adverse events, limiting its use in certain populations. Conclusion: WHO-recommended smallpox vaccines are effective and relatively safe, with MVA-BN considered the most optimal option. Further development of monkeypox-specific vaccines using mRNA and DNA technologies is needed, as these platforms allow more specific antigen targeting and may enhance immune response and safety.